The United States and South Asia from the Age of Empire to Decolonization A History of Entanglements (Leiden University Press, 2022)
The contributions assembled in this volume present cutting-edge research that examines the network of Indo-American interconnections over a wider time frame. The case studies stretch into the American republic's early decades, hinting at a longer history of mutual influence and exchange, beyond the registers of the American century' of globalization. By bringing together academics working across disciplines ranging from history to cultural and literary studies, comparative religion, political science and sociology, this volume thus foregrounds and historicizes the complex, multi-sited, polyvalent nature of the Indo-US encounter. At the same time, the book explores the possibilities of methodologically engaging with established categories-such as the nation, the imperial and Empire-and test alternative typologies to understand this encounter better. Taken together, our authors reconstruct the myriad ways in which Americans and Indians have engaged with each other through trade, diplomacy, intellectual comradeship, missionary evangelism and revolutionary fervor.